Analysis of Fish Consumption Patterns of Budikdamber Households in Poklahsar Bankid Sejahtera, Kediri City - Dwi Sofiati; Asyifa Anandya; Pudji Purwanti; Mochammad Fattah; Fasmadhio Bintang Satryawan (Grouper, 2025)
Fish consumption pattern is a composition of the type and amount of food consumed by a person at a certain time as well as various information that provides an overview of the type and amount of fish eaten. This study aims to determine the pattern of fish consumption and the level of fish consumption in catfish budikdamber households. This type of research uses descriptive with interview, survey, observation and questionnaire methods. The research was determined by purposive sampling with 30 respondents. The results showed that the types of fish that are often consumed are catfish, tilapia and gourami, the average frequency of fish consumption is 12-17 times / month, the average amount of fish purchases is 6-10 kg / month with an average number of family members of 4 people. The average fish consumption level is still relatively low at 1.57 kg/capita/month and 18.84 kg/capita/year.